Impact of income inequality on carbon-intensive extractivism - Hyangsuk Cho (Cogent Economics & Finance, 2023)
In recent decades, lower emissions have been driven by structural changes such as the shift from manufacturing to the service sector and investment in energy efficiency. However, many developing countries extract fossil fuels from the Earth's surface, to export raw materials such as coal, oil, and natural gas in the global market. "Extractivism" is a mode of economic growth currently practiced by many developing countries. This way of economic growth can influence the income distribution and composition of activities that contribute to environmental degradation. Therefore, rent-seeking on fossil fuel export can lead to income inequality and a carbon-intensive economy. The relationship between carbon intensity and fossil fuel rent, which is the main concern of this paper, was first studied by Friedrichs and Inderwildi (2013) using the concept of the carbon curse. This paper follows similar model to carbon curse theory; however, it presents a new approach by examining the augmented the carbon curse theory through the lens of income inequality. Accordingly, this paper examines how extractivism affects the relationship between income distribution and carbon intensity for 137 countries from 1990 to 2014. Our findings show that countries that are highly dependent on oil rents have a higher degree of unequal income distribution and carbon-intensive developmental pathways. Additionally, there exists a unidirectional causality relationship among oil rents, income inequality, and carbon intensity. Finally, the short-run effect of oil fuel rents on income inequality typically continues in the long run but the effects changes for carbon intensity.
Keywords: 330; carbon curse; Carbon intensity; carbon-intensive way; income inequality; oil rents